PEMANFAATAN LAHAN KOSONG SEBAGAI PENERAPAN TEKNOLOGI MELALUI KEGIATAN KKN TEMATIK - Hazen Arrazie Kurniawan; Risnawati Risnawati; Nurhajijah Nurhajijah; lubis lubis; Tasya seva (Universitas Mataram, 2023)
Desa Pemata Johar is one of the destination villages for thematic KKN activities. This village has become a destination because the Pematang Johar village government is very concentrated on developing the potential of the village, one of the potentials of the Pematang Johar village that needs to be developed is the use of empty land belonging to residents in the framework of producing food in the form of vegetables. Purpose of activity: The purpose of this activity is to optimize abandoned narrow land as a location for food production in the form of vegetables. In this activity, the community was introduced to planting methods that do not require large areas of land but produce maximum results and are easy to make. Activities are carried out using a Participatory Rural Appraisal approach, lecture methods, demonstration plots and mentoring. The results achieved in this verticulture making program were that previously there was a lot of used bottle waste lying around unused now it has become useful and also now the residents' yards have become more useful in order to add value to the beauty of the village and economic income. The results achieved are appropriate technology that utilizes vacant land and used waste as a medium for planting vegetables. Vegetables that are harvested can be sold by local residents or cooked for themselves. In addition, the harvest time for vegetable crops is shorter so that residents do not have to wait long for the results of the vertical planting carried out in Thematic KKN activities. Based on the activities that have been carried out, it can be concluded that PKK women and residents in the village of Pematang Johar are very enthusiastic and want to take advantage of the vacant land for vertical cultivation. With this activity, you can increase knowledge and skills in the community through the Thematic KKN activity programs